Advances in the mechanism and therapeutic potential of neutrophil extracellular traps in cancer promotion - Li, Xiaorui; Wang, Huilin; Li, Jingchang; Li, Chuangchuang; Zhao, Shuo; Wang, Qing; Ren, Weihong (Frontiers in Oncology, 2025)
Neutrophil extracellular traps (NETs) are chromatin-based structures containing histones and granular proteases released during NETosis. They constitute a key antimicrobial defense mechanism while exposing pathogenic histones. While NET components effectively eliminate microorganisms, their pro-inflammatory and cytotoxic properties inflict significant damage on host endothelial cells and tissues. This damage contributes to diverse pathologies, including autoimmune diseases where NET-derived components act as autoantigens, as well as circulatory disorders, diabetes, and especially, cancer. Recent research has increasingly illuminated the critical connection between NETs and cancer progression, highlighting their role in promoting tumor development across all stages through inflammation and tissue injury. Consequently, targeting NET composition, formation, or release has emerged as a promising therapeutic strategy. These approaches effectively mitigate NET-mediated pathogenesis while circumventing the drawbacks of direct neutrophil depletion. Although translating these strategies into widespread clinical practice presents challenges, experimental studies demonstrate significant potential. This review examines the mechanisms by which NETs drive cancer, explores current therapeutic applications targeting NETs, and discusses both the prospects and challenges of this evolving anticancer approach.